Ni-based 3D hierarchical heterostructures achieved by selective electrodeposition as a bifunctional electrocatalyst for overall water splitting. (20th May 2021) - Li, Youjun; Dastafkan, Kamran; Sun, Qiangqiang; Ma, Yi; Wang, Xiuhang; Yang, Xueying; Wang, Zenglin; Zhao, Chuan
Abstract: The fabrication of efficient, cost-effective and stable bifunctional electrocatalysts for electrocatalytic water splitting is an important way of energy conversion and storage. In this work, ultrathin NiFe alloy layers are coated on the surface and the up-sidewalls of the Ni(Cu) nanotubes by a selective electrodeposition and used as a bifunctional electrocatalyst. Having a 3D honeycomb-like structure, superlarge ECSA of Ni(Cu)/NF and NiFe alloy films simultaneously fabricated on the surface of Ni foam, the NiFe@Ni(Cu)/NF catalyst shows a Pt-like performance in hydrogen evolution reaction and efficient oxygen evolution reaction activity in alkaline medium. The fabricated NiFe@Ni(Cu)/NF electrode delivers current densities of 10 mA cm −2 at overpotentials of merely 36 and 209 mV for HER and OER. Furthermore, the water electrolysis cell assembled with the as-prepared catalyst requires an energy input as low as 1.525 V to deliver 10 mA cm −2 . The bifunctional NiFe@Ni(Cu)/NF also presents remarkable stability in alkaline solution with negligible degradation rate in potential. This study provides a new approach for rational design of hetero-hierarchical structures of bifunctional electrocatalysts for energy storage and conversion applications.